281. Prostate artery embolization of benign prostate hyperplasia: Technical and dosimetric aspects. (December 2018) - Roberto, E.; Quaranta, S.; De Maggi, A.; Bergesio, F.; Bongiovanni, S.; Grosso, M.; Chauvie, S.
Abstract : Purpose: The aim of this work was to optimize technical and dosimetric aspects of Prostate Artery Embolization (PAE) for Benign Prostatic Hyperplasia (BPH). Methods: The radiological procedures in PAE consist of an angio-CT on a Brillance64 (Philips, Eindhoven, The Netherlands) to define the anatomical vascular structure of pelvis and of prostatic arteries and the angiographic procedure on the Integris Allura system (Philips, Eindhoven, The Netherlands) or in the hybrid room with the Zeego system (Siemens, Forchheim, Germany). The latter performs rotational acquisition that permits 3D CT-like reconstructions. Combining the angiographic acquisition with the anatomical 3D reconstruction of CT permits to map the prostatic artery during the procedure. An evaluation of the ESD, pESD, and effective dose was performed based on the dose-area product (DAP), weighting contributions of all the different projections. Results: 21 consecutive patients with a mean age of 75.5 (range 56–93) years were studied: 12 with Allura and 9 with Zeego. Effective doses were 54 (range 25–81) mSv during imaging and 46 (range 16–85) mSv during fluoroscopy with Allura and 37 (8–68) mSv during imaging and 80 (33–175) mSv during fluoroscopy with Zeego. Zeego permits a decrease in latero-lateral, contralateral and PA projections, compensated by the rotational acquisition. The effective dose in angio-CT was 7.9 (3.4–18.9) mSv. Optimization by reducing the number of frames per projection and the size of the field in the district of interest pemitted to lower the dose of 35%. Average ESD and pESD were respectively 0.62 Gy and 1.02 Gy on Zeego and respectively 0.44 Gy and 1.49 Gy on Zeego. The rotational dose for Zeego was evaluated 6.8% of the total dose. The angio-CT contributed to the 6.7% of the total dose. Conclusions: In this work we gave a first report on the effective dose delivered during PAE on two different generations angiographics system. More patient are needed to understand the advantage of the different technologies.